Oxygen Evolution Behavior of PTFE-F-PbO2 Electrode in H2SO4 Solution - 童少平 张铁明 马淳安 (Chinese journal of chemical engineering, 2008)
F-PbO2 electrode and polytetrafluoroethylene （PTFE） doped F-PbO2 electrode （PTFE-F-PbO2） were prepared on a plexiglas sheet substrate by a series of procedure including chemical and electrochemical depositions. The electrochemical activities of these two electrodes for oxygen evolution （OE） reaction were examined by electrochemical tests. In comparison with F-PbO2, PTFE-F-PbO2 electrode exhibited larger active surface area and higher oxygen vacancy deficiency, which resulted in its higher electrocatalytic activity for OE. In addition, both exchange current density and activation energy of the electrodes for OE were calculated in terms of active surface area. The values of exchange current density and activation energy in 0.5 mol·L^-1 H2SO4 aqueous solution were 1.125×10^ -3 mA·cm^-2 and 18.62 kJ·mol^-1 for PTFE-F-PbO2, and 8.384×10^-4 mA·cm^- 2 and 28.98 kJ·mol^-1 for F-PbO2, respectively. Because these values are calculated on the basis of the active surface areas of the electrodes, the enhanced activity of PTFE-F-PbO2 can be attributed to an increase in oxygen vacancy deficiency of PbO2 due to doping by PTFE. The influence of PTFE adulteration on the activity of PbO2 film electrode for OE was investigated in detail in this study.